Human evolutionary genetics - Jobling, Mark; Jobling, Mark A.; Jobling, Mark A. (New York : Garland Science, 2014)
'Now in full color, this new edition of Human evolutionary genetics has been brought up-to-date with the many advances and discoveries made since the publication of the highly regarded first edition. The focus of the book is human genetic diversity: the mechanisms that generate it, how we study it, its implications in evolution, and its implications today. It will be an invaluable resource for anyone studying human evolution, genetic variation, population genetics, and biological anthropology'--
An introduction to human evolutionary genetics -- Organization and inheritance of the human genome -- Human genome variation -- Finding and assaying genome diversity -- Processes shaping diversity -- Making inferences from diversity -- Humans as apes -- What genetic changes have made us human? -- Origins of modern humans -- The distribution of diversity -- The colonization of the old world and Australia -- Agricultural expansions -- Into new-found lands -- What happens when populations meet -- Understanding the past, present, and future of phenotypic variation -- Evolutionary insights into simple genetic diseases -- Evolution and complex diseases -- Identity and identification.
Revised edition of: Human evolutionary genetics / Mark A. Jobling, Matthew Hurles, Chris Tyler-Smith. c2004.
Includes bibliographical references and index.
Keywords: Human genetics -- Variation; Human evolution; Human molecular genetics; Evolution, Molecular; Adaptation, Biological; Anthropology, physical; Genetic Variation; Genome, Human